Perbandingan Tingkat Pengembalian (Return), Risiko dan Koefisien Variasi Pada Saham Syariah dan Saham Non Syariah di Bursa Efek Indonesia (BEI) Periode 2011-2013 - Ajeng Gama Rosyida; Imron Mawardi (Universitas Airlangga, 2015)
The purpose of this study was to determine the differences of rate of return, risk and coefficient of variation on Islamic stock and non-Islamic stock in Indonesia Stock Exchange (IDX) 2011-2013. This study was using quantitative approach with Mann-Whitney U test. The population in this study was Islamic stock and non-Islamic stock which listed on Indonesia Stock Exchange (IDX) within the time period (2011-2013). Determination of the number of samples using probability sampling, where the sampling randomly taken from members of the population without considering the level, and 10 Islamic stock and 10 non-Islamic stock where being selected. Data that being used was secondary data. The data was collected from official website of the Indonesia Stock Exchange (IDX). The results of this study showed that there was no significant differences of rate of return, risk and coefficient of variation on Islamic stock and non-Islamic stock.